2017
DOI: 10.1111/his.13392
|View full text |Cite
|
Sign up to set email alerts
|

The epithelioid BAP1‐negative and p16‐positive phenotype predicts prolonged survival in pleural mesothelioma

Abstract: In conclusion, p16 IHC is an independent prognostic biomarker in pleural mesothelioma. When used in combination with BAP1 IHC and morphological subtyping, patients with exceptionally prolonged survival can potentially be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…27 In addition, we observed a doubling of the median survival (6.5 versus 3.5 mo) and a three-fold increase in survival at 12 months (30% versus 10%), compared with historical controls for sarcomatoid mesothelioma. 1,26 Although response assessment in mesothelioma is challenging, and reported infrequently in trials for the nonepithelioid disease, the 93.5% disease control rate is encouraging and consistent with the earlier dose-escalation study findings. 12 Collectively, these data benchmarked the design of the ATOMIC-meso (ADI-PEG 20 Targeting Of Malignancy Induces Cytotoxicity-Mesothelioma) study, which transitioned from phase 2 to phase 3 earlier this year after successful recruitment of 176 patients with nonepithelioid mesothelioma; a further 210 patients are being enrolled to report on the primary end point of OS (ClinicalTrials.gov identifier NCT02709512).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…27 In addition, we observed a doubling of the median survival (6.5 versus 3.5 mo) and a three-fold increase in survival at 12 months (30% versus 10%), compared with historical controls for sarcomatoid mesothelioma. 1,26 Although response assessment in mesothelioma is challenging, and reported infrequently in trials for the nonepithelioid disease, the 93.5% disease control rate is encouraging and consistent with the earlier dose-escalation study findings. 12 Collectively, these data benchmarked the design of the ATOMIC-meso (ADI-PEG 20 Targeting Of Malignancy Induces Cytotoxicity-Mesothelioma) study, which transitioned from phase 2 to phase 3 earlier this year after successful recruitment of 176 patients with nonepithelioid mesothelioma; a further 210 patients are being enrolled to report on the primary end point of OS (ClinicalTrials.gov identifier NCT02709512).…”
Section: Discussionsupporting
confidence: 72%
“…23,24 Moreover, twice as many patients were alive at 15 months with biphasic compared with the epithelioid disease (40% versus 20%), indicating that the latter subgroup is at the aggressive end of the spectrum and concurring with the poor-prognosis epithelioid disease defined by nuclear grading and p16 loss on multivariate analysis. 25,26 Notably, the 8.2 month median OS for nonepithelioid disease compares favorably with the recent SWOG S0905 trial reporting a median OS of 6.3 months for PemCis plus placebo or 6.5 months for PemCis plus the vascular endothelial growth factor receptor antagonist, cediranib (n ¼ 23; nonepithelioid). 27 In addition, we observed a doubling of the median survival (6.5 versus 3.5 mo) and a three-fold increase in survival at 12 months (30% versus 10%), compared with historical controls for sarcomatoid mesothelioma.…”
Section: Discussionmentioning
confidence: 62%
“…According to our results, BAP1 was relatively insensitive marker (low sensitivity of 44.6%) in detecting malignant mesothelioma. Our results matched those of Nasu et al, 2015;; Righi et al, 2016;Hida et al, 2017;Yoshimura et al, 2017;Chou et al, 2018;Kinoshita et al, 2018(b), andYoshimura et al, 2019, who all reported low BAP1 sensitivity, ranging from 50-65%.…”
Section: Discussionsupporting
confidence: 91%
“…The type (domestic, environmental or occupational), intensity and period of asbestos exposure, as well as genetic predisposition might impact on clinical characteristics of MPM patients and their prognosis [40]. Further analyses need to explore if this is rather a reflection of indolent biology or also a consequence of treatment efficacy [41][42].…”
Section: Discussionmentioning
confidence: 99%